The impact of agricultural production on the emissions of greenhouse gases and the directions to re- duce them in the Republic of Belarus - Bertosh, Evgeniya; Narkevich, Ivan (Journal of the Belarusian State University. Ecology, 2024)
The assessment of greenhouse gas emissions is the basis for fulfilling of the international obligations of countries that have ratified the United Nations Framework Convention on Climate Change and the Paris Agreement, including the Republic of Belarus. The results of its assessment are required for the preparation of the Greenhouse Gas Emissions Inventory Reports, goals for reduction of greenhouse gas emissions and the development of national long-term low- carbon strategies until 2050. Currently, the Republic of Belarus does not have a comprehensive document defining long-term directions for the reducing of greenhouse gas emissions in r various sectors of the economy, the adoption of which is necessary, in particular, for the implementation of the requirements of the Paris Agreement. Some of the measures for reduction of greenhouse gas emissions activities have been implemented by programs and strategies for the development of individual sectors of the economy for the next five-year period for 2021–2025 and up to 2030. In particular, it is expected to ensure greenhouse gas emissions in 2030 below the 1990 emission level by 35–40 % through the implementation of various measures to improve the energy efficiency of the national economy, resource saving, development and implementation of technologies of waste management, sustainable forest use. Measures to reduce greenhouse gas emissions in agriculture within the framework of the national goal to reduce greenhouse gas emissions have not yet been considered. At the same time, agriculture has a significant impact on greenhouse gas emissions and its contribution to national emissions is constantly increasing. Therefore, it is necessary to develop and implement certain measures to reduce greenhouse gas emissions in this sector. The purpose of this article is to analyze greenhouse gas emissions resulting from agricultural production over the period 1990–2021. For this purpose, the main sources of greenhouse gas emissions in agriculture have been identified, and priority areas for reducing of anthropogenic impact have been proposed that can be laid down for to the national strategy of low-carbon development of the Republic of Belarus.
Keywords: greenhouse gases; low-carbon development; sustainable agriculture; measures to reduce emissions; carbon farming; climate-smart technologies